Bacterial colonization and TH17 immunity are shaped by intestinal sialylation in neonatal mice. (12th February 2022) - Irons, Eric E; Cortes Gomez, Eduardo; Andersen, Valerie L; Lau, Joseph T Y
Abstract: Interactions between the neonate host and its gut microbiome are central to the development of a healthy immune system. However, the mechanisms by which animals alter early colonization of microbiota for their benefit remain unclear. Here, we investigated the role of early-life expression of the α2, 6-sialyltransferase ST6GAL1 in microbiome phylogeny and mucosal immunity. Fecal, upper respiratory, and oral microbiomes of pups expressing or lacking St6gal1 were analyzed by 16S rRNA sequencing. At weaning, the fecal microbiome of St6gal1 -KO mice had reduced Clostridiodes, Coprobacillus, and Adlercreutzia, but increased Helicobacter and Bilophila . Pooled fecal microbiomes from syngeneic donors were transferred to antibiotic-treated wild-type mice, before analysis of recipient mucosal immune responses by flow cytometry, RT-qPCR, microscopy, and ELISA. Transfer of St6gal1- KO microbiome induced a mucosal Th17 response, with expression of T-bet and IL-17, and IL-22-dependent gut lengthening. Early life intestinal sialylation was characterized by RT-qPCR, immunoblot, microscopy, and sialyltransferase enzyme assays in genetic mouse models at rest or with glucocorticoid receptor modulators. St6gal1 expression was greatest in the duodenum, where it was mediated by the P1 promoter and efficiently inhibited by dexamethasone. Our data show that the inability to produce α2, 6-sialyl ligands contributes to microbiome-dependent Th17 inflammation, highlighting a pathway by which the intestinal glycosylation regulates mucosal immunity.